2000
DOI: 10.1073/pnas.120166397
|View full text |Cite
|
Sign up to set email alerts
|

Severe deficiencies in dopamine signaling in presymptomatic Huntington's disease mice

Abstract: In Huntington's disease (HD), mutation of huntingtin causes selective neurodegeneration of dopaminoceptive striatal medium spiny neurons. Transgenic HD model mice that express a portion of the diseasecausing form of human huntingtin develop a behavioral phenotype that suggests dysfunction of dopaminergic neurotransmission. Here we show that presymtomatic mice have severe deficiencies in dopamine signaling in the striatum. These include selective reductions in total levels of dopamine-and cAMP-regulated phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
212
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(245 citation statements)
references
References 51 publications
(54 reference statements)
29
212
3
Order By: Relevance
“…For example, in 4-to 6-week-old presymptomatic R6͞2 mice, expression of certain striatal signaling genes, as well as proteins important for neurotransmission, is significantly reduced (54)(55)(56)(57). In addition, marked striatal and cortical neuron atrophy is detectable at 6 weeks of age (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 4-to 6-week-old presymptomatic R6͞2 mice, expression of certain striatal signaling genes, as well as proteins important for neurotransmission, is significantly reduced (54)(55)(56)(57). In addition, marked striatal and cortical neuron atrophy is detectable at 6 weeks of age (42).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is evidence to show that HD symptomatology occurs before extensive striatal cell death (54)(55)(56)(57), and apoptosis tends to be an acute, rather than chronic, process. In fact, in the initial characterization of the R6͞2 Tg HD mouse, no significant cell death was detected.…”
Section: Discussionmentioning
confidence: 99%
“…DARPP-32 is highly enriched in medium-sized spiny neurons and its down-regulation is an early marker of neuronal dysfunction in HD (40). Normalization of motor behavior in GM1-treated YAC128 mice correlated with increased striatal expression of DARPP-32 ( Fig.…”
Section: Chronic Infusion Of Gm1 Restores Normal Motor Behavior In Yamentioning
confidence: 99%
“…Several reports have shown that these mice reproduce some of the dopaminergic dysfunction observed in HD patients. However, dopaminergic deficits are more apparent in the R6/2 line (Bibb et al 2000;Hickey et al 2002;Petersen et al 2002), which shows a more rapid progression of HD symptoms (Mangiarini et al 1996). These dopaminergic alterations include decreased levels of D 1 and D 2 dopamine receptors (Cha et al 1998), reduced dopamine content (Reynolds et al 1999), and age-dependent impairment in the behavioural response to dopamine stimulants (Hickey et al 2002).…”
mentioning
confidence: 99%